2018
DOI: 10.1175/mwr-d-18-0300.1
|View full text |Cite
|
Sign up to set email alerts
|

A Background Investigation of Tornado Activity across the Southern Cumberland Plateau Terrain System of Northeastern Alabama

Abstract: The effects of terrain on tornadoes are poorly understood. Efforts to understand terrain effects on tornadoes have been limited in scope, typically examining a small number of cases with limited observations or idealized numerical simulations. This study evaluates an apparent tornado activity maximum across the Sand Mountain and Lookout Mountain plateaus of northeastern Alabama. These plateaus, separated by the narrow Wills Valley, span ~5000 km2 and were impacted by 79 tornadoes from 1992 to 2016. This area r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A Getis Ord Gi* hotspot analysis was performed in ArcGIS. The analysis identified areas of significant geographic clustering of cyclogenesis for storms that produce either heavy (hot spot) or light (cold spot) snowfall totals in Central New York (Figure 3) (Getis and Ord, 1992; Lyza and Knupp, 2018; Saunders et al ., 2018). The number of storms forming in each grid cell was then calculated and a Getis Ord Gi* hotspot analysis was again used, this time to determine typical areas of cyclogenesis (Figure 3).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…A Getis Ord Gi* hotspot analysis was performed in ArcGIS. The analysis identified areas of significant geographic clustering of cyclogenesis for storms that produce either heavy (hot spot) or light (cold spot) snowfall totals in Central New York (Figure 3) (Getis and Ord, 1992; Lyza and Knupp, 2018; Saunders et al ., 2018). The number of storms forming in each grid cell was then calculated and a Getis Ord Gi* hotspot analysis was again used, this time to determine typical areas of cyclogenesis (Figure 3).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Rapid scan, mobile radar data from four tornadoes that occurred in the U.S. plains region are analyzed. While this area of the country generally does not have particularly high topographic relief, Lyza and Knupp (2014) determined that topographic elevation changes as small as 20 m had an impact on tornado intensity in their study, and Karstens et al (2013) found similarly that elevation changes as small as 30 m were impactful. Such conditions are commonly found throughout the central plains and in the study domain (Figs.…”
Section: Introductionmentioning
confidence: 73%
“…This site was selected to align with the objectives of VORTEX-SE pertaining to terrain influences on tornadogenesis. Scottsboro is located west (nominally upstream) of the southern Cumberland terrain range (known locally as Sand Mountain), where a regional maximum in tornadogenesis events has been documented (Lyza and Knupp 2018). UMass FMCW operated at Scottsboro from 10 March to 1 May 2017, with only a few gaps in data coverage (Frasier et al 2017) (Fig.…”
Section: The Umass Fmcw Radar a Instrument Descriptionmentioning
confidence: 99%
“…In our implementation, at each UMass FMCW observation time, the 08C height was derived from the Atmospheric Emitted Radiance Interferometer (AERI; Knuteson et al 2004a,b) optimal-estimation (AERIoe; Turner and Löhnert 2014) product of the Collaborative Lower Atmospheric Profiling System (Wagner et al 2019). CLAMPS was collocated with UMass FMCW for both the 2016 and 2017 VORTEX-SE field campaigns (Turner , 2017Lyza et al 2018). The CLAMPS temperature profiles are derived from downwelling radiance measurements collected by the onboard AERI, and have root-mean-square errors of less than 1.0 K in clearsky conditions up to 5 km AGL when compared with radiosonde temperature profiles (Turner and Löhnert 2014).…”
Section: November 2019mentioning
confidence: 99%